Heart rate variability in chronic pain patients: a study on gender differences - SANJEEV K. SINGH; ATANU ROY; AK TIWARI; PB SINGH (International Journal of Pharma and Bio Sciences, 2017)
Various studies have been conducted showing the effects of chronic pain on HRV but the same study has not been conducted yet in the Eastern Uttar Pradesh. Present study was conducted to assess the effects of chronic pain on HRV. The patients were chosen from the Pain Clinic with chronicity of > 6 months duration and severity of > 3 on visual analogue scale. The age-sex matched controls were also selected. ECG was recorded in the resting state and was analyzed for the HRV. Max RR interval, Min RR interval, SDNN, RMSSD, pNN50 and mean RR interval in male cases is significantly different than the same parameters of female cases (p < 0.05). The frequency domain parameters are not different in male cases and male controls than the female cases and female controls respectively except L.F.ms2. The observations reveal that the sympathetic tone has either increased or remained normal and the parasympathetic tone has decreased in both, male and female cases indicating the shifting of sympathovagal balance in the sympathetic side. Though the gender related responses are not very consistent, but it can be concluded that the HRV responses are different in males than the female groups.